Triptolide Attenuates Vascular Calcification by Upregulating Expression of miRNA-204 - Pei, Yu-qiang; Zheng, Yong-qiu; Ding, Yao-dong; Xu, Qi-xiang; Cao, Di; Wu, Ya-ning; Wang, Rui; Yang, Jia-xin; Liang, Jing; Ma, Qian; Ge, Hai-long (Frontiers in Pharmacology, 2021)
Background: Triptolide (TP), a natural product of Tripterygium wilfordii, has been shown to protect against cardiovascular system, but the molecular mechanisms underlying its protective function are not fully understood. In this present study, we sought to test the potential protective role of TP in the regulation of vascular calcification in a rat model and explored whether TP attenuates medial vascular calcification by upregulating miRNA-204 (miRNA204). Methods: A vascular calcification (VC) model of rat aorta was induced with vitamin D3 plus nicotine (VDN). Von Kossa and HE staining were applied to assess the degree of calcification of rat aortas. Alkaline phosphatase (ALP) activity and calcium content were measured. miRNA-204 expression was quantified by quantitative reverse-transcription polymerase chain reaction (qRT-PCR). The localization of bone morphogenetic protein-2 (BMP2) and runt-related transcription factor-2 (RUNX2) expression were detected by immunohistochemistry and western blotting. Results: Administration of TP greatly reduced vascular calcification in a dose-dependent manner compared with VC controls. The increase in ALP activity and calcium content was ameliorated by TP. Moreover, protein expression levels of BMP2 and RUNX2 were significantly reduced in calcified aortas. miRNA-204 expression was increased in the TP-treated groups compared with VC controls and the effects of TP were reversed by the intravenous injection of miRNA-204-interfering lentivirus. Conclusion: TP inhibited BMP2 and RUNX2 expression and attenuated vascular calcification via upregulating the level of miRNA-204. TP appears to be a potential new therapeutic option for treating vascular calcification.